Nitrogen Tax and Set-Aside as Greenhouse Gas Abatement Policies Under Global Change Scenarios: A Case Study for Germany - Martin Henseler; Ruth Delzeit; Marcel Adenäuer; Sarah Baum; Peter Kreins (Environmental and Resource Economics, 2020)
The ambitious climate policy objectives of the COP21 agreement require the design and the implementation of effective and efficient policy instruments. The effectiveness and efficiency of agricultural abatement options depend on regional climate and natural conditions, changes in the global economy, global agricultural markets and regional agricultural production. Thus, the assessment of abatement options requires consideration of the global scale, the market scale and the regional producer scale. We investigate two abatement options discussed controversially in literature. Both have been partially applied to reduce environmental pollution from agriculture: a tax on nitrogen and the obligatory set-aside of agricultural land. Our study provides an assessment of the ecological effectiveness and the economic efficiency of both abatement options under different global scenarios. In our policy analysis we combine three applied policy simulation models to develop an integrated economic model framework. This model framework considers the global, the national and the regional scale and consists of the global general equilibrium model DART-BIO, the partial-equilibrium model CAPRI and the regional supply model RAUMIS. In the different global scenarios, the results show that both abatement options create relatively high marginal abatement costs and that the maximally reached abated greenhouse gas emissions represent only 15% of the quantity required to fulfill the policy targets. Compared to the obligatory set-aside option, the nitrogen tax is in both scenarios the more efficient policy. With respect to impacts on production and environment, a nitrogen tax is less forecastable than the obligatory set-aside option. Our study illustrates the relevance of considering global economic and market change in the assessment of producer-targeting environmental policies.
Keywords: 330; Greenhouse gas abatement; Environmental policies; Agriculture; Global scenarios; Integrated modelling